PREVALENCE OF DENTAL CARIES, TRAUMATIC DENTAL INJURIES AND UNMET RESTORATIVE TREATMENT NEEDS AMONG SCHOOL CHILDREN OF UDUPI CITY - NITYA CHHABRA,; ISHA SINGH,; SAURAV BHADURI,; KALYANA CHAKRAVARTHY PENTAPATI, (International Journal of Pharma and Bio Sciences, 2016)
Aim: We aimed to evaluate the dental caries, traumatic dental injuries (TDI) and unmet restorative treatment needs (URTN) among the school children of Udupi district and to compare these parameters between public and private school children. Materials and methods: A cross-sectional study was done among 9-15 year old school children of 4 government and 4 private schools of Udupi district. Demographic information like age, gender, type of school along with caries status and traumatic dental injuries were recorded. All clinical examinations were evaluated in school premises under natural lighting conditions using mouth mirrors and CPI probes as per WHO guidelines (1997).Results: A total of 792 school children were examined out of which 50.8% were males. A total of 24.2% (n=292) and 47.9% (n=279) children had caries in primary and permanent dentition with mean of 0.42±0.88 and 1.13±1.5 respectively. A total of 6% of the subjects had TDI (5.4% in enamel and 0.6% in dentin fracture). Absolute number of teeth with unmet treatment needs for restorations, prosthesis and extractions were 1290, 4 and 15 respectively. The mean decayed teeth in permanent and primary dentition was significantly higher in public school children than private school children (p=0.001 and 0.001) respectively. The restorative need calculated from decayed teeth and traumatic dental injuries was significantly higher than the restorative need calculated from decayed teeth only (p<0.001).Conclusion: Almost half of the school children had caries experience in the permanent dentition. Traumatic dental injuries constitute significant proportion of restorative need and should be included in the assessment of unmet restorative need.